Economic Vulnerability of Small Producers Due to Income Uncertainty and Institutional Asymmetry - Fatmawati Sungkawaningrum; Navirta Ayu; Mohamad Abdul Munjid (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the economic vulnerability of small-scale producers in Indonesia by analyzing the effects of income uncertainty and institutional asymmetry, while incorporating regulatory certainty as a mediating variable and the internalization of moral values as a moderating variable. The study aims to explain how structural, regulatory, and ethical dimensions influence the sustainability and resilience of small-scale producers. Design/methodology/approach – This study employed a quantitative approach using a survey design involving small-scale producers in Indonesia. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the direct, mediating, and moderating relationships among income uncertainty, institutional asymmetry, regulatory certainty, moral value internalization, and economic vulnerability. Finding/Results – The findings reveal that institutional asymmetry has a strong positive and significant effect on economic vulnerability, indicating that structural market inequality is the primary determinant of vulnerability among small-scale producers. In contrast, income uncertainty does not have a significant direct effect on economic vulnerability, as reflected by the near-zero path coefficient. However, its influence operates indirectly through regulatory certainty as a mediating mechanism. Furthermore, the internalization of moral values moderates the relationship between institutional asymmetry and economic vulnerability by strengthening producers’ adaptive capacity and resilience toward structural market pressures. Originality/Value – This study contributes to the literature by integrating regulatory certainty and moral value internalization into a comprehensive structural model of economic vulnerability among small-scale producers. The findings emphasize the importance of inclusive market institutions, regulatory certainty, and ethical-economic values in reducing inequality and strengthening long-term economic sustainability.